(untitled) (Bodhi Path, 2020)
The ultimate goal is to achieve Perfect Enlightened One, The Buddha by practising Meditation technique particularly Vipassanā Sadhanā in Buddhist Tradition. The prince and son of the King Suddhodhana of Kapilavaṭṭhu, Siddhartha Gautama renounced the kingly palace and comforts of the life in search of eradication of suffering. He had gone through the teachings and preaching of Ācaryā Alāra Kalama and Ācaryā Rāmaputta Udareka honestly and meticulously but not satisfied because he was intending to search the path that eradicate sufferings of all sentient beings and moved further in search of the ultimate truth that path succeed in eradication of suffering of all human race, towards the forest of Urevellā on the Bank of river Niranjanā. He meditated spontaneously and impulsively to achieve the goal in the dark forest where sun light did not approached the earth even in the day. The air create storm so strong that trees got crash one another and generate a blunder sound. Bodhisattva Siddhartha and his other five colleagues, who joined him there, were meditated and meditated day and night continuously nearly for six years but no avail. Bodhisattva Siddhartha had not surrendered before the Māra even he became so thick and thin that if he touched his stomach, he touched his spinal cord and when he touched his back, he touched his stomach. The his five colleagues left him all alone there when they saw that the Bodhisattva had milk food (Pāyasa) by hands of Sujatā and after that they moved towards Sarnātha near Varanasi. Siddhartha also took bath in the river Niranjanā and after crossing the river he came in Urevellā now this place is known as Bodhagayā and he meditated with strong determination under the Pipal Tree (Bodhi Tree) and ultimately achieved Enlightenment on Veśāka Day. Thereafter he become The Buddha, the Enlightened one, the awaken one. He came to know the subtle to subtlest points of the meditation including these impediments or hindrances (the five Nivarna) in achieving Nibbāna and also come to know how to overcome these miseries. He came to know all what were supportive and helping (Bojjhaṅga) and obstacles (Nīvarṇa) in the meditation practice. What were the strong hindrances of the Citta that obstructed the mind in achieving the highest goal and purify of the mind from all kinds of clinging and utmost deliverance from the Cycle of Rebirth, Nibbāna.